Racial discrimination in the life course of older adults experiencing homelessness: results from the HOPE HOME study. Issue 2 (2nd July 2020) - Paul, Dereck W.; Knight, Kelly R.; Olsen, Pamela; Weeks, John; Yen, Irene H.; Kushel, Margot B.
ABSTRACT: Over 2.5 million people experience homelessness yearly in the United States. Black persons are overrepresented by three-fold among those experiencing homelessness but little research has examined the relationship between race and homelessness. We aimed to understand the relationship between race and the experience of homelessness for older adults. We used grounded theory methodology to analyze in-depth qualitative interviews ( n  = 65) of persons experiencing homelessness. We recruited participants who were enrolled in two sub-studies of the Health Outcomes of People Experiencing Homelessness in Older Middle AgE (HOPE HOME) Study in Oakland California. We identified two major themes within interviews with Black participants ( n  = 52) related to race: (1) participants experienced overt racial discrimination in early life and (2) structural racism precipitated and perpetuated adult homelessness. Further, we identified sub-themes of structural racism that contributed to participants becoming or staying homeless: criminal justice discrimination, employment discrimination, exposure to violence, premature death, and limited family wealth. We developed a theoretical model of how these elements of structural racism may increase susceptibility to homelessness. These relationships between racial discrimination and homelessness may serve as targets for policies aimed at preventing homelessness.